Waste Becomes Economic Value: Corn Leather Craft Training for Young Mothers in Nagari Lareh Nan Panjang - Putri, Lili Dasa; Jamaris, Jamaris; Solfema, Solfema; Natsir, MHD; Irmawita, Irmawita; Defi, Tri Assifa Candra; Ahmanda, Ritno (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2025)
This community service program addressed the problem of corn husk waste and limited economic opportunities for housewives in Nagari Lareh Nan Panjang, West Sumatra. Corn husks, usually discarded or burned, pose environmental challenges while holding potential as raw material for handicrafts. The activity aimed to empower young mothers by equipping them with practical skills to process corn husks into marketable products, thereby supporting household income and reducing waste. The method applied included a systematic approach consisting of needs assessment, community engagement, training, mentoring, and the formation of home industry groups. Training was conducted over four days, combining theoretical sessions and practical workshops on producing items such as tissue boxes, decorative flowers, and wall ornaments. Mentoring was provided to strengthen product quality, packaging, and digital marketing skills. The results showed significant improvement in participants’ knowledge, skills, and motivation. Several products were successfully created, and a community-based business group was established with official recognition from the local government. The program not only enhanced household income but also fostered environmental awareness and community cooperation. Overall, the initiative proved effective as a sustainable empowerment model that combines environmental management with economic development.Keywords: community empowerment, corn husk waste, handicraft training, women’s economic development, sustainable livelihood.